Orthoflavivirus circulation in South-East Queensland, Australia, before and during the 2021–2022 incursion of Japanese encephalitis virus assessed through sero-epidemiological survey of a sentinel equine population - Nicholas K.Y. Yuen; Jessica J. Harrison; Althea S.W. Wang; Isabella E. McMahon; Gervais Habarugira; Mitchell P. Coyle; Helle Bielefeldt-Ohmann (One Health)
An incursion and outbreak of Japanese encephalitis virus (JEV) was reported in Australia in 2021 and 2022, respectively. There was speculation that JEV may have been circulating in Australia unknowingly prior to the detection. In this study, we determined sero-prevalence and transmission of West Nile virus (WNV), Murray Valley encephalitis virus (MVEV) and JEV, prior to and post JEV incursion in a sentinel equine population in south-east Queensland (SEQ), Australia, using blocking ELISAs (screening test) and virus neutralisation test (confirmatory). Serum samples collected between 2018 and 2020 (prior to JEV incursion; n = 607) from horses residing in SEQ revealed that sero-prevalence to pathogenic orthoflaviviruses was low, specifically WNV (1.3 %; 8/607), MVEV (1.2 %; 7/607), and JEV (4.9 %; 30/607). The significantly higher prevalence of JEV (P < 0.05) was skewed by the high proportion of horses previously enrolled in one or more JEV vaccine studies (17/30; 56.7 %) and the unknown JEV vaccination history due to international travel (6/30; 20 %). Thirty-two foals were enrolled as sentinels to monitor for arbovirus transmissions in SEQ between 2020 and 2023. Results showed that JEV seroconversion was first detected in April 2022 (n = 4), with seven more seroconversions detected in the following months until November 2022. This study (i) confirms that it is highly unlikely that JEV incursion in SEQ occurred prior to February 2022; (ii) circulation of WNV in SEQ remains very low; and (iii) highlights the complexity in the interpretation of orthoflavivirus serological results. The authors propose that horses should be included as sentinels for arbovirus transmission monitoring in Australia.